Physical Activity Is Associated With Sleep Quality: Results of the ESSE-RF Epidemiological Study - Dubinina, Elena; Korostovtseva, Lyudmila S.; Rotar, Oxana; Amelina, Valeria; Boyarinova, Maria; Bochkarev, Mikhail; Shashkova, Tatiana; Baranova, Elena; Libis, Roman; Duplyakov, Dmitry; Sviryaev, Yurii; Konradi, Aleksandra; et al. (Frontiers in Psychology, 2021)
Background and hypothesis: Physical activity (PA) is an important behavioral factor associated with the quality of life and healthy longevity. We hypothesize that extremely low and extremely high levels of daily PA (including occupational PA) may have a negative impact on sleep quality and psychological well-being. Objective: The aim of the study is to investigate the association between the level and type of PA and sleep problems in an adult population. Materials and methods: The study sample included participants from the population-based cohort of The Epidemiology of Cardiovascular Risk Factors and Diseases in Regions of the Russian Federation Study (ESSE-RF). The data of three regions (Saint-Petersburg, Samara, Orenburg), varying in geographic, climatic, socioeconomic characteristics, was included into analysis. The total sample comprised 4800 participants (1600 from each region; 1926 males, 2874 females), aged 25-64. The level of PA was evaluated using three parameters: the type of PA at work, the frequency of an intensive/high PA including sport (times a week), the mean duration of leisure-time walking (minutes a day). The measures of sleep quality were sleep duration and the frequency of difficulty falling asleep, difficulty maintaining sleep, daytime sleepiness, and sleep medication use. PA and sleep characteristics were assessed by interview carried by the trained medical staff. Results: When controlling for gender, age and socioeconomic status (SES) extremely high occupational PA was a significant risk factor for difficulty falling asleep 3 or more times a week (OR[CI95%]=2.2[1.4-3.4], p=0.001) while working in a sitting position or having moderate physical load at work were not associated with sleep characteristics. Having a high physical load 6 or more times a week was a risk factor for difficulty falling asleep controlling for gender, age and SES (OR[CI95%]=1.5[1.1-2.2], p=0.01) and also after controlling additionally for a high physical load at work (OR[CI95%]=1.6[1.1-2.4], p=0.02). The association between leisure-time walking and sleep characteristics was insignificant. Walking less than an hour a day was associated with increased depression scores (46.5% versus 41.9%, p=0.006)). Conclusion: High physical load at work and excessively frequent intensive PA are associated with difficulties initiating sleep and may represent a risk factor for insomnia.